Total and inorganic arsenic contents in some edible Zingiberaceous rhizomes in Thailand - Chomkamon Ubonnuch (2018)
The arsenic accumulation in rhizomes of Zingiberaceous plants was determined by atomic absorption spectrometry interfaced with hydride generation system (HG-AAS). The raw herbal materials, rhizomes, were collected from different regions of Thailand between December 2011 and January 2012. Six well-known Zingiberaceous plants, 16 samples from each and a total of 96 samples, were analyzed Alpinia galanga (Khaa), Boesenbergia rotunda (Kra-chaai), Curcuma longa (Khamin-chan), Curcuma zedoaria (Khamin-oi), Zingiber cassumunar (Plai) and Zingiber officinale (Ginger). Concentrations of total arsenic based on dry weight were 92.4 ± 9.2, 103.5 ± 20.8, 61.7 ± 12.5, 89.8 ± 17.5, 106.7 ± 19.5 and 69.3 ± 11.8 ng/g, respectively and inorganic arsenic were 48.8 ± 7.0, 66.3 ± 12.7, 25.5 ± 5.0, 38.7 ± 4.7, 71.2 ± 11.6, and 38.5 ± 5.5 ng/g, respectively. Among these, Plai and Kra-chaai exhibited the highest levels of total arsenic and inorganic arsenic accumulation that remind consumers to be aware of excess consuming of these rhizomes. On the contrary, the lowest value found in Khamin-chan indicating natural dietary supplements and herbal medicines comprising Kamin-chan are safe from arsenic poison. All investigated amounts of total and inorganic arsenic were much lower than limits recommended by Thai Food and Drug Administration. © 2013 Chomkamon Ubonnuch et al.